Класифікація рослинності та біотопів: проблеми, рішення, перспективи. Друга Всеукраїнська науково-теоретична конференція - Дідух, Я.П.; Дубина, Д.В.; Чусова, О.О. (Український ботанічний журнал, 2016)
У статті представлені результати роботи Другої Всеукраїнської науково-теоретичної конференції «Класифікація рослинності та біотопів України як наукова основа збереження біорізноманіття», що відбулася 14–15 березня 2016 р. в Інституті ботаніки імені М.Г. Холодного НАН України. Доповіді учасників зібрання були присвячені трьом темам: класифікації рослинності України в контексті підготовки широкомасштабної класифікації рослинності Європи (EuroChecklist) та продромусу рослинності України; створенню синтаксономічної бази даних (UkrVeg) як основи розроблення класифікації рослинності та біотопів України та її інтеграції до European Vegetation Archive (EVA), Global Index of Vegetation-Plot Data base (GIVD); біотопам України, їх класифікації, використанню для функціонування екомережі і збереженню біорізноманітності та протидії впливу негативних наслідків змін довкілля. Конференція виявила низку проблем, які потребують негайного розв'язання. Це – необхідність створення повноцінної бази даних геоботанічних описів рослинності України (UkrVeg), яка б репрезентувала всі класи рослинності, а також уніфікація ключових понять, термінів, визначень, що стосуються біотопів і інших категорій, які суттєво ускладнюють розуміння їхньої суті. Конференція прийняла відповідну резолюцію та накреслила основні напрямки розвитку геоботаніки в Україні. В статье представлены результаты работы Второй Всеукраинской научно-теоретической конференции «Классификация растительности и биотопов Украины как научная основа сохранения биоразнообразия», состоявшейся 14–15 марта 2016 г. в Институте ботаники имени Н.Г. Холодного НАН Украины. Доклады участников форума были посвящены трем темам: классификации растительности Украины в контексте подготовки широкомасштабной классификации растительности Европы (EuroChecklist) и продромуса растительности Украины; созданию синтаксономической базы данных (UkrVeg) как основы разработки классификации растительности и биотопов Украины и ее интеграции в European Vegetation Archive (EVA), Global Index of Vegetation-Plot Data base (GIVD); биотопам Украины, их классификации, использованию для функционирования экосети и сохранению биоразнообразия, а также противодействию влияния негативных последствий изменений окружающей среды. Конференция выявила ряд проблем, требующих немедленного разрешения. Это – необходимость создания полноценной базы данных геоботанических описаний растительности Украины (UkrVeg), которая представляла бы все классы растительности, а также унификация ключевых понятий, терминов, определений, касающихся биотопов и других категорий, существенно затрудняющих понимание их сути. Конференция приняла соответствующую резолюцию и обозначила основные направления развития геоботаники в Украине. Results of the Second Ukrainian Scientific-theoretical Conference “Classification of vegetation and habitats of Ukraine as a scientific basis for biodiversity conservation” held on March 14–15, 2016 are presented. The Conference was organized by M.G. Kholodny Institute of Botany, NAS of Ukraine (Department of Geobotany and Ecology) and the Ukrainian Botanical Society (section of Geobotany and Ecology). There were three main topics of the presentations at the Conference: classification of vegetation of Ukraine in the context of preparation of large-scale classification of vegetation of Europe (EuroChecklist) and the Checklist of vegetation of Ukraine; development of the syntaxonomic database (UkrVeg) as a basis of the vegetation and habitat classification of Ukraine and its integration into European Vegetation Archive (EVA), Global Index of Vegetation-Plot Database (GIVD); habitats of Ukraine, their classification, use in ecological network functioning, biodiversity conservation and counteraction of negative effects on the environment. The conference revealed a number of problems that need to be solved. It is necessary to create a complete database of geobotanical descriptions of vegetation of Ukraine (UkrVeg), which would represent all classes of vegetation and unified key concepts, terms, definitions regarding the habitats and other categories. The Conference adopted a resolution and outlined the main directions of geobotany in Ukraine.